23n+5n-24n-4n+10n-3=17

Simple and best practice solution for 23n+5n-24n-4n+10n-3=17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 23n+5n-24n-4n+10n-3=17 equation:


Simplifying
23n + 5n + -24n + -4n + 10n + -3 = 17

Reorder the terms:
-3 + 23n + 5n + -24n + -4n + 10n = 17

Combine like terms: 23n + 5n = 28n
-3 + 28n + -24n + -4n + 10n = 17

Combine like terms: 28n + -24n = 4n
-3 + 4n + -4n + 10n = 17

Combine like terms: 4n + -4n = 0
-3 + 0 + 10n = 17
-3 + 10n = 17

Solving
-3 + 10n = 17

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 10n = 17 + 3

Combine like terms: -3 + 3 = 0
0 + 10n = 17 + 3
10n = 17 + 3

Combine like terms: 17 + 3 = 20
10n = 20

Divide each side by '10'.
n = 2

Simplifying
n = 2

See similar equations:

| I=1000-40r | | 10/8=8x/10 | | -2(x-6)/7=35 | | 2y=3x+21 | | 90=22.50c | | y=2x^4-4x^2-48 | | 1/3x-9=8 | | -52=4z | | 3k-74=2k-8 | | -9+5(6h-3)= | | f(x)=2x^4-4x^2-48 | | f(x)=(-3)(-1)-2 | | 9k+k-5k-k+5=45 | | H-2=-12 | | 3c+5=16c-99 | | 6(-7+9y)= | | 14k+25=4k+95 | | 15/16x-11/19y=-3 | | (5x^6+8y^2)(5x^6+8y^2)= | | 2x+3=4cx+5 | | 5(3x+1)=7(5x+7)+2 | | 89j+4=23j+70 | | 4/3(3.14/1)(5832/1)= | | -8-4(2+8k)= | | 10(y-1)=-2(6+y) | | 3.14(36)(18)= | | -9(-2-8g)= | | -40=-5Y | | 2x^2+19x=32 | | 5x+7-4x=-21 | | 5x-24+3x+36=35+6x-2 | | 2x+5y=17-4x |

Equations solver categories